Respostas
respondido por:
1
Método da Adição:
x + y = 2
3x + y = - 2 ( - 1)
x + y = 2
- 3x - y = 2 (+)
------------------
- 2x = 4 (-1)
2x = - 4
x = -4/2
x = - 2
x + y = 2
- 2 + y = 2
y = 2 + 2
y = 4
R.: x = - 2 e y = 4
x + y = 2
3x + y = - 2 ( - 1)
x + y = 2
- 3x - y = 2 (+)
------------------
- 2x = 4 (-1)
2x = - 4
x = -4/2
x = - 2
x + y = 2
- 2 + y = 2
y = 2 + 2
y = 4
R.: x = - 2 e y = 4
respondido por:
2
X + Y = 2 . (-1)
3X + Y = -2
- X - Y = -2
3X + Y = -2
2X = -4
X = -4/2
X = -2
X + Y = 2
-2 + Y = 2
Y = 2 + 2
Y = 4
V= {-2, 4}
3X + Y = -2
- X - Y = -2
3X + Y = -2
2X = -4
X = -4/2
X = -2
X + Y = 2
-2 + Y = 2
Y = 2 + 2
Y = 4
V= {-2, 4}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás